Extrusion foaming of semi-conductive poly (lactic acid)/carbon nanotube nanocomposites: Processing and foam microstructure correlations - Estaji, Sara; Jafari, Aidin; Farahani, Saba; Saeidi, Ardeshir; Nobre, Marcos A. L. [UNESP]; Hemmati, Farkhondeh; Khonakdar, Hossein Ali (My University, 2025)
In this study, semiconductive poly (lactic acid) (PLA)/carbon nanotube (CNT) nanocomposites have been simultaneously subjected to melt-compounding and foaming using a continuous and single-step extrusion foaming process. The extrusion foaming process with the ability to be developed on an industrial scale is a complex process for a biopolymer in the presence of nanoparticles, chemical foaming agent, and chain extender, and to control it, knowledge about the phenomena occurring during the process and the structural properties of the foam is required. Although the extrusion foaming of PLA has been studied before, the simultaneous effects of chain extender content and nanoparticle loading on the microstructure and phenomena during the PLA extrusion foaming process have not been thoroughly investigated. The results of this study show that the two investigated variables have a strong interaction with each other. Increasing the chain extender content has led to a change in the rheological properties of the melt, as a result, it has been significantly effective in the nanoparticle dispersion state. Besides, the loading of nanoparticles has a powerful effect on the intensity of the chain extension reaction of PLA chains by the chain extender additive. The lightest extruded foams (with a void fraction of 0.52) with the highest cell density (5 × 106 cells/cm3), the smallest cell size (about 50 and 200 µm for number- and volume-average cell diameters), and the most uniform cell size distribution have been obtained in the middle values of the chain extender content (5 phr) and the lowest values of the nanoparticle loading (0.25 phr).
Keywords: biopolymer; Extrusion; foam; nanocomposite